Risk Factors for Mortality among HIV/AIDS Patients - Zaki Mita Kusumaadhi; Nur Farhanah; Muchlis Achsan Udji Sofro (Diponegoro International Medical Journal, 2021)
Background: Morbidity and mortality of HIV/AIDS infections is still high and as  a global health problem particularly in Low-Middle Income Countries (LMICs). Indonesia ranks third in Asia Pacific in increasing HIV infection. A Study on risk factors for mortality in HIV/AIDS patients in Dr. Kariadi General Hospital has never been conducted. This study analyzed the risk factors for mortality among HIV/AIDS patients.Methods: Case control study, data from medical records of inpatients and outpatients in Dr. Kariadi General Hospital from January 2015 to December 2017.Results: Study subject: Two hundred and ten HIV/AIDS patients, were included; 105 (56.75%) as cases and 105 (9.65%) control patients. The significant risk factors for mortality were as follow: male sex (p = 0.030); age ≥ 45 years (p = 0.035); non compliance to treatment (p = 0,000); WHO clinical stage III and IV (p = 0,000); co-infection of pulmonary tuberculosis (p = 0,000); CD4 cell count < 200 cells/mm3 (p = 0,000); eGFR < 60 mL/minute/1.72 m2 (p = 0.001) and Haemoglobin level < 10 g/dL (p = 0.008). The non-significant risk factors for mortality were as follow: level of education (p = 0.650); Hepatitis B co-infection (p = 0.153) and Hepatitis C co-infection (p = 0.506). The most important risk factors for mortality in this study in were non compliance to treatment (p = 0.003; OR = 3.285) and CD4 count < 200 cells/mm3 (p = 0.014; OR = 5.480).Conclusion: In this study, the risk factors for mortality in HIV/AIDS patients were male sex; age ≥ 45 years; non compliance to treatment; WHO clinical stage III and IV; co-infection of pulmonary tuberculosis, CD4 count < 200 cells/mm3; eGFR < 60 mL/minute/1.72 m2 and Hb level < 10 g/dL. The most important risk factors for mortality were non compliance to treatment and CD4 count < 200 cells / mm3.